PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI KASUS STAFF KARYAWAN PT. SUBAINDO CAHAYA POLINTRACO SURABAYA) - INDRIYANTI PERMATA, CINDY (Jurnal Ilmu Manajemen (JIM), 2017)
Cahaya Buana Group is a company engaged in furniture manufacturing. Up to now Cahaya Buana Group has 27 branch companies, and the only branch company in the eastern part of Indonesia is PT. Subaindo Cahaya Polintraco. Employee performance at PT. Subaindo Cahaya Polintraco is influenced by several factors such as job satisfaction and organizational commitment. The company will look to its success if it gets employee job satisfaction and organizational commitment.This study aims to examine and analyze the effect of job satisfaction on employee performance through organizational commitment as intervening variable (Case Study of Employee Staff at PT Subaindo Cahaya Polintraco). The object of this research is one of manufacturing companies in Surabaya. The sample of this research is 73 staff of employees in accounting department, marketing, production, and Human Resource Management (HRD). The sample technique used is a saturated sample. Data analysis method in this research is using Partial Least Square (PLS). The result of research on hypothesis testing is that job satisfaction have positive and significant effect to employee performance, job satisfaction have positive and significant influence to organizational commitment, organizational commitment have positive and significant impact to employee performance, and organizational commitment can mediate job satisfaction on employee performance positively and significantly. Thus, the research is expected to be a reference for companies in managing Human Resources at PT. Subaindo Cahaya Polintraco Surabaya. Keywords: Job Satisfaction, Organizational Commitment, Employee Performance